Observation of mating behaviour in Phayre’s Langur (Trachypithecus phayrei) in Lawachara National Park, Bangladesh (Bangladesh Journal of Zoology, 2025)
Abstract not AvailableBangladesh J. Zool. 53(1): 125-129, 2025